Kinamycin biosynthesis employs a conserved pair of oxidases for B-ring contraction1. Issue 42 (25th May 2015) - Wang, Bin; Ren, Jinwei; Li, Liyuan; Guo, Fang; Pan, Guohui; Ai, Guomin; Aigle, Bertrand; Fan, Keqiang; Yang, Keqian
<x xml:space="preserve">Abstract</x> A conserved pair of oxidases is characterized as nature's machinery for benzofluorenone formation.